AB1365 Proprotein convertase subtilisin/kexin type 9 (PCSK9) in patients with systemic lupus erythematosus/lupus nephritis. (12th June 2018) - Fang, C.; Luo, T.; Lin, L.
Abstract : Background: SLE patients have a tendency of accelerated atherosclerosis(AS) which can only partly be explained by traditional risk factors for cardiovascular disease. Proprotein convertase subtilisin/kexin type 9 (PCSK9), which is a protease associated with cardiovascular risk that regulates both cholesterol metabolism and inflammatory reaction, had been regarded as a highly promising therapeutic target for cardiovascular disease[. 1 Recent study had demonstrated that SLE patients with lupus nephritis(LN) had much higher risk of atherosclerosis[. 2 Objectives: To assess serum PCSK9 concentrations and the possible factors linked with PCSK9 variation in SLE/LN patients. Methods: 47 SLE patients and 30 healthy controls were included. Traditional cardiovascular risk factors were compared. According to cIMT, SLE patients were divided into two subgroups (SLE-AS subgroup and SLE-NonAS subgroup, cut-off point is 1.0 mm). PCSK9 concentrations were compared between: 1 SLE patients and controls; 2 SLE-AS subgroup and SLE-NonAS subgroup; 3 SLE patients with and without lupus nephritis(LN). The correlational analyses between PCSK9 levels and disease parameters were undergone. Results: The differences of lipids parameters, body mass index (BMI), uric acid(UA) between SLE group and controls had no statistical significance. Even so, the ratio of cIMT thickening were higher in SLE patients, when compared with healthy controls (23.40% versus 6.67%, p=0.05). Serum PCSK9 levels were also significantly elevated in SLE patients than controls (median of PCSK9 level: 390.53 ng/ml versus 292.44 ng/ml, p <0.05). Patients in SLE-AS subgroup had even higher PCSK9 and C-reactive protein(CRP) levels than those in SLE-NonAS subgroup (median of PCSK9 level: 516.41 ng/ml versus 364.47 ng/ml, p<0.05; median of CRP level: 4.56 mg/L versus 1.05 mg/L, p<0.01) (figure 1). PCSK9 levels correlated with CRP levels, but not with age, disease activity, lipids characteristics, BMI or UA levels, particularly in female patients (table 1). Despite of no statistical significance, the ratio of lupus nephritis were higher in SLE-AS subgroup than those in SLE-NonAS subgroup (63.64% versus 44.44%, p>0.05). SLE patients with LN had higher PCSK9 concentrations than those without LN evidence(509.53±131.69 ng/ml versus 332.02±92.72 ng/ml, p <0.001). Conclusions: Elevation of PCSK9 concentrations can be observed in SLE patients, especially in those with LN or atherosclerosis. PCSK9. PCSK9 is probably linked with low-grade inflammation participating in the pathogenesis of atherosclerosis in SLE/LN patients. References: [1] Robinson JG, Farnier M, Krempf M, et al. Efficacy and safety of alirocumab in reducing lipids and cardiovascular events[J]. N Engl J Med. 2015Apr 16;372(16):1489–99. [2] McHugh J. Systemic lupus erythematosus: Atherosclerosis confined to patients with nephritis[J]. Nat Rev Rheumatol. 2017Jun;13(6):322. Acknowledgements: The authors thank Qiulan Li and Hongzhi Gao for the excellent technical assistance. Disclosure of Interest: None declared